2014
DOI: 10.1364/oe.22.030092
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects in thin-film organic solid-state lasers

Abstract: Abstract:With the recent development of organic solid-state lasers (OSSLs) architectures enabling power scaling and progresses towards continuous-wave operation, the question of thermal effects now arises in OSSLs. In this paper, a Rhodamine 640-PMMA based vertical external cavity surface emitting organic laser is investigated. A thermal microscope is used to record temperature maps at the organic thin film surface during laser action; those maps are compared with time-resolved finite element thermal simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The largest temperature increase was only 3 °C even when the highest excitation power of 1290 mW cm −2 was used. This suggests that heat‐induced degradation is negligible under photoexcitation fluence used in this study, which agrees with a previous report …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The largest temperature increase was only 3 °C even when the highest excitation power of 1290 mW cm −2 was used. This suggests that heat‐induced degradation is negligible under photoexcitation fluence used in this study, which agrees with a previous report …”
Section: Resultssupporting
confidence: 93%
“…A low laser threshold of 1.0 µJ cm −2 was demonstrated from 4‐dicyanomethylene‐2‐methyl‐6‐sp‐dimethylaminostyryl‐4H‐pyran (DCM) doped into a tris(8‐hydroxyquinoline)aluminum (Alq 3 ) host film . Since then, organic laser performance has significantly improved from the development of new gain materials, device architectures, and triplet managing materials and clarification of the underlying physics of laser oscillation …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thermal effect by the optical pumping will not be so large. While the TO coefficient of general organic compounds is as large as ∼ 10 −4 K −1 [33], it has been shown that, under the pulsed pumping with low repetition ratio (<50 Hz), the rise in sample temperature is suppressed as low as 0.8 K [34]. This cannot induce the significant wavelength shift as observed in our experiments.…”
Section: Resultsmentioning
confidence: 46%
“…Here, it can be seen that the wavelength, and thus, the refractive index of the water sucrose solution, is increasing from left to right as the sucrose is added on the left. The stable wavelength level before sucrose is added confirms that wavelength blue shifts induced by temperature changes 31,32 are weak for the devices used and can be neglected here. Some of the pixels at later points in time remain unchanged.…”
Section: Resultsmentioning
confidence: 55%